Prevalence and risk factors for antenatal anxiety in the first trimester among Chinese pregnant women - Li Zhang; Yan Zhang; Jin Liu; Yan Yu; Junzhe Cheng; Yumeng Ju; Mi Wang; Bangshan Liu; Shuyin Xu; Mengqi Xu; Yilin Peng; Jintao Xiong; et al. (General Psychiatry)
Background Antenatal anxiety (AA) is a common mental disorder during pregnancy and adversely affects the well-being of both pregnant women and their offspring. The prevalence of AA is exceptionally high in the first trimester, yet there is a lack of studies focusing exclusively on AA in the first trimester.Aims This study aimed to investigate the prevalence and risk factors of AA among Chinese pregnant women during the first trimester.Methods We retrospectively retrieved and analysed data on the mental health screening of perinatal women at Shenzhen Baoan Women’s and Children’s Hospital in China from 1 January 2020 to 31 January 2024. A total of 42 013 pregnant women with less than 14 weeks of gestation were assessed using the 7-item Generalized Anxiety Disorder Scale (GAD-7). A GAD-7 score ≥10 indicates AA. Univariable analyses and multivariable logistic regression were employed to identify risk factors for AA.Results Among the participants, 1066 (2.54%) experienced AA in the first trimester. Factors associated with a higher risk of AA included being under 25 years old, temporary residence, below senior high school education, low or moderate economic status, primipara, unplanned pregnancy, smoking, alcohol use, lack of exercise, low or moderate living conditions, low or moderate marital satisfaction and reluctance to discuss troubles with others.Conclusions AA manifests as a multifaceted phenomenon influenced by various sociodemographic, obstetrical, lifestyle and psychosocial factors. Preventing AA requires collaboration among hospitals, communities and families.